Septal Perforation Repair Using Polydioxanone Plates. Issue 4 (October 2015) - Sand, Jordan P.; Desai, Shaun C.; Branham, Gregory H.
<x xml:space="preserve">Abstract</x> Summary: Medium to large septal perforations are a challenging problem to the rhinoplasty surgeon. In this study, records and outcomes are reviewed for 25 patients who underwent septal perforation repair over a 10-year period. All patients underwent an open septorhinoplasty approach with use of bilateral opposing mucoperichondrial flaps and a unique intervening graft that included acellular dermis, temporalis fascia alone, or a novel closure technique using temporalis fascia and a polydioxanone plate. The authors identify that for medium to large septal perforations, the use of the polydioxanone plate with temporalis fascia provided the highest rate of closure as a method of scaffolding a fascial graft, and also provided ease of placement between opposing mucoperichondrial flaps. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.